Challenging Mobilities in and to the EU during Times of Crises The Case of Greece - Kousis, Maria; Chatzidaki, Aspasia; Kafetsios, Konstantinos (IMISCOE Research Series,, 2022)
This open access book offers a cross-disciplinary view of challenging mobility issues for migrants and refugees in Europe and particularly Greece during the last decade when the economic and refugee crises coincided. It offers new analyses and data on a diverse range of topics concerning new emigrants as well as refugees and mobilities in Greece. The book covers themes which are not only related to refugee and immigrant integration and governance challenges, but also describes host attitudes, solidarity, political and protest claims in the public sphere, as well as the changing emigration environment in Greece within a European context. With contributions from the fields of philosophy, anthropology, sociology, economics, political science, geography and linguistics, this book provides a unique resource for students and scholars, but also for policy-makers and social scientists working on migration-related issues within and beyond Europe.